1998
DOI: 10.1006/viro.1998.9156
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization and Some Biochemical Properties of the Flavivirus Kunjin Nonstructural Proteins NS2A and NS4A

Abstract: In a previous study on the replication of Kunjin virus using immunoelectron microscopy (E. G. Westaway, J. M. Mackenzie, M. T. Kenney, M. K. Jones, and A. A. Khromykh, 1997, J. Virol. 71, 6650-6661), NS1 and NS3 were found associated with double-stranded RNA (dsRNA) within vesicle packets (VP) in infected Vero cells, suggesting that these induced membrane structures may be the cytoplasmic sites of RNA replication. NS2B and NS3 (comprising the virus-encoded protease) were colocalized within distinct paracrystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
306
3
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 288 publications
(329 citation statements)
references
References 48 publications
16
306
3
4
Order By: Relevance
“…Translation and replication of flaviviruses occurs in close association with cellular membranes (Mackenzie et al, 1998;Welsch et al, 2009;Westaway et al, 1997Westaway et al, , 1999Westaway et al, , 2003. The viral proteins associated with the replication complex are the two hydrophobic viral proteins, NS2A and NS4A, the abundant luminal protein NS1, and the NS5 and NS3 proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Translation and replication of flaviviruses occurs in close association with cellular membranes (Mackenzie et al, 1998;Welsch et al, 2009;Westaway et al, 1997Westaway et al, , 1999Westaway et al, , 2003. The viral proteins associated with the replication complex are the two hydrophobic viral proteins, NS2A and NS4A, the abundant luminal protein NS1, and the NS5 and NS3 proteins.…”
Section: Introductionmentioning
confidence: 99%
“…The flavivirus NS2A protein is~25 kDa, hydrophobic, membrane-associated protein shown to be involved in RNA replication (Mackenzie et al, 1998;Rossi et al, 2007), membrane permeabilization (Chang et al, 1999), virion formation (Kümmerer & Rice, 2002;Leung et al, 2008;Liu et al, 2003), viral dissemination from mosquito midgut (McElroy et al, 2006) and regulation of host antiviral responses (Liu et al, 2005(Liu et al, , 2006. Our previous work demonstrated that a single amino acid substitution from alanine to proline at position 30 (A30P) of the NS2A gene attenuated virus virulence in mice and inhibited the virus' ability to downregulate type I interferon (IFN-a/b) production (Liu et al, 2006).…”
mentioning
confidence: 99%
“…It was reported that NS2A binds with high specificity to the 3' untranslated region (UTR) of viral genomic RNA and to other components of the replication complex (Mackenzie et al, 1998). In addition, NS2A is considered to play roles in modulating the host-antiviral interferon response (Liu et al, 2004;Liu et al, 2006;Liu et al, 2005;Munoz-Jordan et al, 2003) and assembly/ secretion processes of virus particles (Kummerer and Rice, 2002;Leung et al, 2008;Liu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%